Evaluation of the apogeotropic posterior canal benign paroxysmal positional vertigo: case studies from a tertiary clinic perspective - Zhi Jian, Alex Ho; Jamaluddin, Saiful Adli; Al-Hadeethi, Yahia F. Hussein; Othman, Iylia Ajmal; Zainudin, 'Ismah Syazana (Malaysian Medical Association (MMA), 2025)
Benign paroxysmal positional vertigo (BPPV) is a prevalent vestibular disorder characterised by intermittent vertiginous episodes due to dislodged otoconia predominantly affecting the posterior canal. Atypical variants like apogeotropic posterior canal BPPV (aPC-BPPV) present diagnostic challenges and are likely underreported, particularly in Malaysia. We present two cases of aPC-BPPV. The first involves a 57-year-old female with persistent vertigo, initially misdiagnosed as right anterior canal BPPV. Video head impulse testing (VHIT) revealed reduced VOR gain in the right posterior canal, and the Demi-Semont manoeuvre successfully resolved her symptoms. The second case is a 62-year-old female, also misdiagnosed with left anteriorcanal BPPV. VHIT confirmed left posterior canalinvolvement, and repeated Demi-Semont manoeuvres led tosymptom resolution. These cases highlight the intricatediagnostic challenges associated with aPC-BPPV, especiallyin differentiating it from contralateral anterior canal BPPV.Conventional diagnostic methods may yield incorrectresults, emphasising the importance of incorporatingadvanced tools like VHIT as an ancillary assessment forprecise canal identification. Atypical nystagmus andpersistent symptoms after standard treatment warrant re-evaluation, with unresolved anterior canal (AC-BPPV) casesreferred to a tertiary centre, as they may represent aPC-BPPV. Effective management often requires repeated, canal-specific manoeuvres such as the Demi-Semont, which haveshown greater success in relieving symptoms in aPC-BPPVcases. Accurate diagnosis and targeted treatment arecrucial for managing atypical BPPV. Improved awarenessand advanced diagnostic methods, such as VHIT, canenhance outcomes, especially in cases where atypicalpresentations are not well-documented.